2010
DOI: 10.4172/2150-3508.1000014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Water Temperatures on the Utilisation Efficiencies of Energy and Protein by Juvenile Barramundi, Lates calcarifer

Abstract: This study was undertaken to define the effects of temperature on the energy and protein partial utilisation efficiencies of juvenile Barramundi. The experiment used a factorial design with four temperatures (25ºC, 29ºC, 32ºC, and 36ºC) and three ration levels (low, moderate, satiety) to examine the response of Barramundi to varying digestible energy (DE) and digestible protein (DP) intake. Energy and protein deposition with varying intakes at most temperatures were linear, though aberrations occurred at 36ºC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…However, in a more recent study in cobia with initial body weights between 10 and 200 g for 21 days, Sun and Chen () suggested a higher optimum temperature (33°C) for rearing cobia for these fish sizes, which resulted in the highest SGRs that varied between 2.39 and 6.43. Temperature above the optimum causes increased faecal production, but reduced feed consumption and feed absorption and feeding efficiency in cobia (Sun et al, ), as well as in other fish (Bermudes, Glencross, Austen, & Hawkins, ; Glencross & Bermudes, ; Sun, Zhang, & Tang, ). A higher FCR in cobia reared at elevated temperature implies that a larger amount of feed would be needed to support the same growth performance as those fish reared at control temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a more recent study in cobia with initial body weights between 10 and 200 g for 21 days, Sun and Chen () suggested a higher optimum temperature (33°C) for rearing cobia for these fish sizes, which resulted in the highest SGRs that varied between 2.39 and 6.43. Temperature above the optimum causes increased faecal production, but reduced feed consumption and feed absorption and feeding efficiency in cobia (Sun et al, ), as well as in other fish (Bermudes, Glencross, Austen, & Hawkins, ; Glencross & Bermudes, ; Sun, Zhang, & Tang, ). A higher FCR in cobia reared at elevated temperature implies that a larger amount of feed would be needed to support the same growth performance as those fish reared at control temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown to what degree and how strongly the metabolism will adapt to a reduced availability of nutrients, there may be altered availability of metabolites such as methionine that may modulate metabolism, energy allocation, appetite, amongst others. It has been reported that thermal stress induces protein degradation, but reduces protein synthesis resulting in impaired growth in fish (Glencross & Bermudes, ; Sun & Chen, ). Meanwhile, dietary methionine supplementation might alleviate the negative impact of thermal stress, as methionine might involve immunological functions (Pan et al, ), and could suppress the expression of genes related to protein degradation, but induce the expression of genes related to protein synthesis, and thus improve the protein deposition (Del Vesco et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The marginal efficiencies of protein (kp) and lipid (kf) of a range of species including Atlantic salmon (Salmo salar), rainbow trout (Oncorhynchus mykiss), European seabass (Dicentrarchus labrax), gilthead sea bream (Sparus aurata), white grouper (Epinephelus aeneus) and yellow-tail kingfish (Seriola lalandi) generally range between kp 0.53 -0.64 and kf 0.72 -0.91 (Booth et al, 2010;Bureau et al, 2006;Helland et al, 2010;Lupatsch et al, 2003). In barramundi, Glencross and Bermudes (2010) showed that over a range of temperatures from 25 to 32˚C the partial efficiency of energy (kpf) was relatively consistent at 0.56 and protein (kf) was relatively consistent at 0.51.Despite the apparent importance of essential fatty acids (EFA) the energetic efficiencies and maintenance requirements of these nutrients do not appear to have been investigated in fish using a bioenergetics approach.…”
Section: Introductionmentioning
confidence: 99%
“…Disparity in requirements of fish for protein and amino acids such as this may be the result of several variables, including differences in the ecological niches of the species (natural habitat affecting the turnover of specific amino acids and/or trophic level influencing the composition of natural food sources or transport of amino acids in the gut) (Ferraris and Ahearn, 1984;Auerswald et al, 1997;Hertrampf and Piedad-Pascual, 2012), fish size or age (Tacon and Cowey, 1985) or experimental design (dietary crude protein level and source (Cowey and Cho, 1993;NRC, 2011), range and spacing of inclusion levels of the amino acid of interest and/or model used to define the requirement (Shearer, 2000); proportions of dietary Met:Cys (as discussed previously), feeding regime (Cowey, 1995), water temperature (Bermudes et al, 2010); and the use of crystalline amino acids and whether these were bound or encapsulated prior to feed production (as also referred to earlier in this chapter)).…”
Section: Metabolic Roles Of the Sulphur Amino Acidsmentioning
confidence: 99%
“…a is a temperature-dependent coefficient and b is the cost in units of DP to deposit one unit of protein as growth (Glencross and Bermudes, 2010;Glencross and Bermudes, 2011).…”
Section: Introductionmentioning
confidence: 99%